Penerapan Lean Six Sigma Dalam Waktu Tunggu Pelayanan Resep Di Rumah Sakit : Studi Literatur - Aghniya Choirunnisa; Risma Pertiwi; Zahra Septina; Acim Heri Iswanto (Pusat Riset dan Inovasi Nasional, 2023)
Long waiting time is one component that has the potential to cause patient dissatisfaction. If the waiting time is long, it will reduce patient comfort and affect patient utility in the future. The method used in this research is Literature Review, namely by collecting and processing research data that has existed before with the 2018-2022 range. The results of this study found that there was a waiting time for drugs, both concoctions and standard drugs, that were not in accordance with the minimum service standards, so that waste was found. There are various types of waste that are found resulting in long drug waiting times such as too many processes to the long process of submitting drug prescriptions to pharmaceutical installations, which causes many inefficient and ineffective activities to arise. Based on this, there is a waiting time for drugs, both concoctions and standard drugs, that are not in accordance with the minimum service standards, so that waste is found. Thus the length of waiting time in preparing the drug is influenced by several factors such as speed and completeness of patient data up to re-submission which takes a lot of time.